Prejudice in School: A Research among Primary School Teachers (European Journal of Education and Psychology, 2008)
The number of immigrants has been continuosly rising, in Italy as well as all around Europe: in Piedmont, the quota of underage immigrants has almost doubled within the last four years, bringing about the issue of educating pupils belonging to different cultures. This research will take into account the opinion of primary school’s teachers on the possible existence of stereotyped or prejudicial opinions about the presence of foreigin children in school and in society, and it will try to understand if it may influence the relationship between teacher and pupil. The 79 teachers and 396 children who took part in this project have been given a questionnaire investigating the occurrence of prejudicial behaviours, and the quality of the relationship created by the teacher with pupils. The data collected show how prejudice appears to influence the relationship teacher-pupil especially in moments of tension, which are worsened by prejudice itself, and how the evaluation of the child may consequently change.Key words: Prejudice, foreign children, teacher-pupil relationship.